Quantifying Intellectual Terrain: Islamic Jurisprudence, Ethical Discourse, and Scholarly Impact - Apriantoro, Muhamad Subhi; Faradilla, Safina; Ashfahany, Afief El; Maruf, Aminudin; Aziza, Nur Amalia (Universitas Muhammadiyah Surakarta, 2024)
This research aims to reveal the trend and development of scientific literature about Islamic law, ethics, and its worldwide significance, spanning the years 1954 to 2023. The utilization of quantitative and network analysis enables the mapping of alterations in publication patterns, the identification of affiliations and highly productive authors, and the highlighting of journals with substantial influence. The findings indicate a significant increase in the number of published works since 1995, particularly in the early 21st century. Notably, the International Islamic University Malaysia and writers El-Seoudi, A.W.M.M. and Jadalhaq, I.M. have made considerable contributions to this surge. The examination of journals emphasizes the significant influence of